Solve for x
x=\frac{\sqrt{6304375986}}{122}-650\approx 0.820497274
x=-\frac{\sqrt{6304375986}}{122}-650\approx -1300.820497274
Graph
Share
Copied to clipboard
1302.13=\left(1586+1.22x\right)x
Use the distributive property to multiply 1.22 by 1300+x.
1302.13=1586x+1.22x^{2}
Use the distributive property to multiply 1586+1.22x by x.
1586x+1.22x^{2}=1302.13
Swap sides so that all variable terms are on the left hand side.
1586x+1.22x^{2}-1302.13=0
Subtract 1302.13 from both sides.
1.22x^{2}+1586x-1302.13=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-1586±\sqrt{1586^{2}-4\times 1.22\left(-1302.13\right)}}{2\times 1.22}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1.22 for a, 1586 for b, and -1302.13 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-1586±\sqrt{2515396-4\times 1.22\left(-1302.13\right)}}{2\times 1.22}
Square 1586.
x=\frac{-1586±\sqrt{2515396-4.88\left(-1302.13\right)}}{2\times 1.22}
Multiply -4 times 1.22.
x=\frac{-1586±\sqrt{2515396+6354.3944}}{2\times 1.22}
Multiply -4.88 times -1302.13 by multiplying numerator times numerator and denominator times denominator. Then reduce the fraction to lowest terms if possible.
x=\frac{-1586±\sqrt{2521750.3944}}{2\times 1.22}
Add 2515396 to 6354.3944.
x=\frac{-1586±\frac{\sqrt{6304375986}}{50}}{2\times 1.22}
Take the square root of 2521750.3944.
x=\frac{-1586±\frac{\sqrt{6304375986}}{50}}{2.44}
Multiply 2 times 1.22.
x=\frac{\frac{\sqrt{6304375986}}{50}-1586}{2.44}
Now solve the equation x=\frac{-1586±\frac{\sqrt{6304375986}}{50}}{2.44} when ± is plus. Add -1586 to \frac{\sqrt{6304375986}}{50}.
x=\frac{\sqrt{6304375986}}{122}-650
Divide -1586+\frac{\sqrt{6304375986}}{50} by 2.44 by multiplying -1586+\frac{\sqrt{6304375986}}{50} by the reciprocal of 2.44.
x=\frac{-\frac{\sqrt{6304375986}}{50}-1586}{2.44}
Now solve the equation x=\frac{-1586±\frac{\sqrt{6304375986}}{50}}{2.44} when ± is minus. Subtract \frac{\sqrt{6304375986}}{50} from -1586.
x=-\frac{\sqrt{6304375986}}{122}-650
Divide -1586-\frac{\sqrt{6304375986}}{50} by 2.44 by multiplying -1586-\frac{\sqrt{6304375986}}{50} by the reciprocal of 2.44.
x=\frac{\sqrt{6304375986}}{122}-650 x=-\frac{\sqrt{6304375986}}{122}-650
The equation is now solved.
1302.13=\left(1586+1.22x\right)x
Use the distributive property to multiply 1.22 by 1300+x.
1302.13=1586x+1.22x^{2}
Use the distributive property to multiply 1586+1.22x by x.
1586x+1.22x^{2}=1302.13
Swap sides so that all variable terms are on the left hand side.
1.22x^{2}+1586x=1302.13
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{1.22x^{2}+1586x}{1.22}=\frac{1302.13}{1.22}
Divide both sides of the equation by 1.22, which is the same as multiplying both sides by the reciprocal of the fraction.
x^{2}+\frac{1586}{1.22}x=\frac{1302.13}{1.22}
Dividing by 1.22 undoes the multiplication by 1.22.
x^{2}+1300x=\frac{1302.13}{1.22}
Divide 1586 by 1.22 by multiplying 1586 by the reciprocal of 1.22.
x^{2}+1300x=\frac{130213}{122}
Divide 1302.13 by 1.22 by multiplying 1302.13 by the reciprocal of 1.22.
x^{2}+1300x+650^{2}=\frac{130213}{122}+650^{2}
Divide 1300, the coefficient of the x term, by 2 to get 650. Then add the square of 650 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+1300x+422500=\frac{130213}{122}+422500
Square 650.
x^{2}+1300x+422500=\frac{51675213}{122}
Add \frac{130213}{122} to 422500.
\left(x+650\right)^{2}=\frac{51675213}{122}
Factor x^{2}+1300x+422500. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+650\right)^{2}}=\sqrt{\frac{51675213}{122}}
Take the square root of both sides of the equation.
x+650=\frac{\sqrt{6304375986}}{122} x+650=-\frac{\sqrt{6304375986}}{122}
Simplify.
x=\frac{\sqrt{6304375986}}{122}-650 x=-\frac{\sqrt{6304375986}}{122}-650
Subtract 650 from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}